Ensaios sobre a rotatividade dos trabalhadores sob a ótica do trabalhador, da empresa e do governo - Ferreira, Allyne de Almeida (2018)
This thesis is composed of three essays on the turnover of workers in the Brazilian labor market, focusing on the three main agents of the economy: workers, companies and the government. The first essay, from the perspective of the worker, sought to analyze if the change in the workers' employment brought wage gains / losses for the formal labor market, during the period from 2010 to 2016, from the data base of the RAIS released by the Ministry of Labor and Employment. By using econometric methodologies (panel data model with fixed effect and quantum regression model for panel data), different results were found on the effect of worker turnover on wages when workers are rotating voluntarily (by worker's decision) and when the workers are involuntary rotary (by decision of the company). In general, the results indicated that voluntary workers (by worker's decision) obtained wage gains, while involuntary workers (by decision of the company) in the lower income quintile suffered wage losses. The second test, from the perspective of the company, sought to analyze the impact of worker turnover on the productivity of companies in the industrial sector, using RAIS data from 2010 to 2016. From the use of linear regression methods for data in panel with fixed effect and the model of quantile regressions for panel data, the results indicated a negative impact of employee turnover on the productivity of companies in the industrial sector. However, when regressions were estimated separately by company size and by quantiles (25th, 50th and 75th), the results of the medium and large companies included in the highest quantile of the distribution showed that the turnover of workers affects positively the productivity of these companies. The third test, from the Government's perspective, sought to assess whether the amendment of the fine of FGTS (Complementary Law 110/2001) from 40% to 50% applied to dismissed workers without just cause altered the dynamics of the dismissals of workers in the labor market. formal work. With RAIS data from 2001 and 2002, descriptive and econometric analyzes, using panel data with fixed effect and quantum regressions for panel data, the results suggested that the implementation of Complementary Law 110/2001 contributed to the decrease in dismissals without just cause may have altered the dynamics of the labor market (dismissal / hiring).